UJI VALIDITAS ASESMEN NUMERASI BERBASIS HOTS PADA MATERI PENGUKURAN PANJANG DAN BERAT UNTUK SISWA KELAS IV SEKOLAH DASAR - Natasya Agustin; Sastrawati, Eka; Zahyuni, Violita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop and validate a Higher Order Thinking Skills (HOTS)-based numeracy assessment on the topic of length and weight measurement for fourth-grade elementary school students. The research employed a research and development approach with validation by material and language experts. Data were collected through interviews, expert validation questionnaires, and documentation. The results of material expert validation showed an overall validity percentage of 80%, categorized as valid, while language expert validation reached 100% with a very valid category. These results indicate that the developed HOTS-based numeracy assessment is appropriate for use in learning and assessment activities in elementary schools.